2015
DOI: 10.1002/admi.201500058
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Femtosecond Laser Doping and Surface Texturing for Implanting Applications

Abstract: titanium surface to reinforce the osseointegration, and provides an antierosion and slow releasing mechanism for antibacterial agents.In this Communication, we report a femtosecond laser doping and surface texturing technology to simultaneously satisfy the above requirements. A thin silver layer was predeposited on the titanium surface and then femtosecond laser was adopted to ablate the composite surface. As a result, not only hierarchical surfaces, i.e., subwavelength nanofringes sitting on microprotrusions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Codoping dental implants with silver by femtosecond laser doping was proposed, obtaining good results [86]. Likewise, Silver-sourced plasma immersion ion implantation (Ag-PIII) was used to modify the surface of stainless steel [87].…”
Section: Antimicrobial Featuresmentioning
confidence: 99%
“…Codoping dental implants with silver by femtosecond laser doping was proposed, obtaining good results [86]. Likewise, Silver-sourced plasma immersion ion implantation (Ag-PIII) was used to modify the surface of stainless steel [87].…”
Section: Antimicrobial Featuresmentioning
confidence: 99%
“…The components of material also influence the use of etching solvent or gas and therefore influence the corresponding etching rate, which further affect the profile of fabricated structures. It has been widely demonstrated that the components of materials can be changed by femtosecond laser induced redox reactions and femtosecond laser doping process [58][59][60][61][62][63] , as shown in Fig. 3.…”
Section: Component Changementioning
confidence: 99%
“…Figures 3(a) and 3(b) show the formation of Ag and Ag clusters inside silver containing zinc phosphate glasses by femtosecond laser irradiation. In addition, it has been demonstrated that semiconductors and metals could be oxidized by laser ablation in air 59,62,63 . Due to the difference of etching rate between silicon and silica, complex three-dimensional microstructures, even suspended microstructures, can be fabricated on these materials 63,64 .…”
Section: Component Changementioning
confidence: 99%
“…LIPSSs are the most unique nanostructures achievable by ultrafast laser ablation at laser fluences no less than the material ablation thresholds. Tuning LIPSSs’ periodicities, orientations, and surface chemistry allows a precise manipulation of the surface color and view-angle iridescence, which opens up the possibilities of LIPSS-based colorful imprinting . We recently discovered that LIPSS can act as a linear-to-circular polarizer to transform linearly polarized light into circular light to induce the formation of irregular triangular and rhombic LIPSSs among normal parallel LIPSSs .…”
Section: Introductionmentioning
confidence: 99%